1985
DOI: 10.1104/pp.77.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Carbon Assimilation in a Shootless Orchid, Chiloschista usneoides (DON) LDL

Abstract: Photosynthetic carbon assimilation in the roots of a shootless orchid Chiloschista usneoides (DON) LDL involves the synthesis and accumulation of malic acid from CO2 in darkness. Malic acid is consumed in the light.The roots do not possess stomata or any means of diurnally regulating the diffusive conductance of the pathway between the internal gas phase ofthe plant and the atmosphere. Regulation of internal CO2 concentration near to atmospheric levels avoids a large net loss of CO2 to the atmosphere during ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 9 publications
2
25
0
1
Order By: Relevance
“…In a study of the leafless orchid Campylocentrum tyrridion, Winter et al (1985) observed a nocturnal increase in titratable acidity content and a daily cycle of CO 2 uptake that resembled classical CAM. Cockburn et al (1985) found similar results in the shootless orchid Chiloschista usneoides. The major acid produced at night was malic acid, which indicates CO 2 uptake via PEPC.…”
Section: Photosynthesis In Aerial Roots Of Shootless Orchidssupporting
confidence: 72%
“…In a study of the leafless orchid Campylocentrum tyrridion, Winter et al (1985) observed a nocturnal increase in titratable acidity content and a daily cycle of CO 2 uptake that resembled classical CAM. Cockburn et al (1985) found similar results in the shootless orchid Chiloschista usneoides. The major acid produced at night was malic acid, which indicates CO 2 uptake via PEPC.…”
Section: Photosynthesis In Aerial Roots Of Shootless Orchidssupporting
confidence: 72%
“…In the Aeridinae, a subtribe of the Epidendroideae comprising approximately 1,350 species, all the members hitherto examined have been shown to express prominent CAM (McWilliams 1970;Goh et al 1977;Avadhani et al 1978;Winter et al 1983;Cockburn et al 1985;Earnshaw et al 1987;Endo and Ikusima 1989). Monophyly of the subtribe was definitely corroborated by phylogenetic analysis by Topik et al (2005).…”
Section: Phylogenetic Constraints On Potential Plasticity Of Cam Exprmentioning
confidence: 84%
“…LUTTGE -t'-^.-Ĉ AM plants, and in particular the atmospheric ones, this represents a crucial mechanism of water acquisition. For leafless and shootless orchids which perform CAM in the green cells of their aerial roots (Cockburn, Goh & Avadhani, 1985;Winter et al, 1985) this mechanism of water uptake may be just as essential. They lack stomata and hence the stomatal responses in the desiccation and starvation dilemma.…”
Section: An = Amalrtmentioning
confidence: 99%